Partisipasi Ibu Rumah Tangga dalam Pengambilan Keputusan Usahatani Tanaman Kacang Panjang di Desa Alebo Kabupaten Konawe Selatan - Salahuddin, Salahuddin; Salam, Idrus; Hendriani, Sutri (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2017)
This study aims to determine the participation of housewives in the introduction, persuasion, decision, confirmation and mother participate in decisions on panajang bean crop farming. This research was used a sample of 35respondents were determined by simple random sampling. This study uses theme thodof measuring the intervalscale. These results indicate that the house wife had a very large participation in the farming and house wives participate in the decision making long bean crop farming.